Telephone‐Administered Interpersonal Psychotherapy by Nurse‐Midwives for Postpartum Depression. (10th March 2016) - Posmontier, Bobbie; Neugebauer, Richard; Stuart, Scott; Chittams, Jesse; Shaughnessy, Rita
Abstract : Introduction: Postpartum depression (PPD) affects 7% to 13% of childbearing women. Access to care may be limited by maternal time constraints and fears of being judged, labeled as mentally ill, and having their infants taken away. The study's objective was to test the feasibility, effectiveness, and acceptability of certified nurse‐midwife telephone‐administered interpersonal psychotherapy (CNM‐IPT) as a treatment for PPD. Methods: A prospective cohort study was conducted from 2010 to 2014. A sample of women meeting Diagnostic and Statistical Manual of Mental Disorders, Version 4, Text Revision (DSM‐IV‐TR) criteria for depression was recruited from 8 obstetric practices employing CNMs in the United States. Forty‐one women in the treatment group received up to eight 50‐minute CNM‐IPT sessions, and 20 in the control group were referred to mental health professionals. The main outcome measure was the Hamilton Rating Scale for Depression. Secondary outcomes included maternal and marital functioning, mother‐infant bonding, social support, and client satisfaction. Results: The Hamilton Rating Scale for Depression at 8 and 12 weeks was significantly lower among women in the treatment group compared to the control group (Week 8, P = .047; Week 12, P = .029). Client satisfaction was high in both groups. While only 5 out of 8 CNM‐IPT counselors continued the intervention until the study's conclusion, CNM‐IPT counselor protocol adherence was high. Discussion: CNM‐IPT is effective and acceptable as a method of reducing the severity of PPD symptoms. Careful assessment of CNM availability is critical to intervention feasibility. Future research is needed to evaluate translation of this intervention into practice.